(untitled) (Journal of the College of Education for Women, 2025)
English Language Teachers have a crucial role in the process of learning and teaching since high-quality teachers lead to excellent educational outcomes. However, it is not easy to prepare proficient teachers in English language who can use English accurately and fluently inside the classroom. Thus, there is a need for specifically tailored training courses to prepare English language teachers qualified linguistically to use the English language in their classes. This study aims to find out the effect of instructing teacher talk and classroom language on EFL student-teachers’ linguistic performance. The sample of this experimental study consists of (60) students, divided into equal control and experimental groups from the fourth stage, Department of English Language, College of Education for Women, University of Baghdad. The study instrument is an observational checklist prepared by the researcher. After ensuring its validity and reliability, it has been used to assess the linguistic performance of the student-teachers during the practicum period. The results obtained by statistical treatment of data have shown that there is a significant difference between the two groups in favor of experimental group. The findings revealed that the student teachers who have instructed with the expressions of teacher talk, and classroom language have achieved a higher level of performance than that of the student teachers who have not instructed. Accordingly, several recommendations and suggestions for further studies have been set forward.